Cost-Effectiveness Analysis of Transanal Irrigation for Managing Neurogenic Bowel Dysfunction in Japan - Atsushi Sengoku; Shinichi Noto; Masashi Nomi; Anton Emmanuel; Tatsunori Murata; Toshiki Mimura (Journal of Health Economics and Outcomes Research)
**Background:** Neurogenic bowel dysfunction (NBD) is a common sequela in Spinal Cord Injury (SCI) patients. Bowel dysfunction symptoms have a significant negative impact on quality of life (QOL) and are often socially disabling. Transanal irrigation (TAI) is a bowel management procedure that significantly mitigates NBD symptoms in patients refractory to standard bowel care (SBC) by reducing the incidence of fecal incontinence, ameliorating constipation, and improving QOL. TAI devices are used across many countries such as the United Kingdom, Germany, and France, and introduction of the devices is being considered in Japan. In this context, a cost-effectiveness analysis specific to Japanese settings is relevant.